IMPLEMENTASI PROGRAM WIRAUSAHA BARU OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MENDUKUNG GERDU KEMPLING KOTA SEMARANG TAHUN 2014 - Kurniasih, Yuni; Santoso, R. Slamet; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2015)
The Government of Semarang through Local Regulation Number 4 of 2008 about poverty reduction in Semarang City which is an acceleration in poverty reduction efforts. The strategy called Gerdu Kempling (Integrated Health, Economy, Education, Infrastructure, and Environment ) and one of the program that is New Entrepreneur Program by Dinas Tenaga Kerja dan Transmigrasi Kota Semarang. This research was meant to find out how the implementation of New Entrepreneur Program by Dinas Tenaga Kerja Dan Transmigrasi that supports Gerdu Kempling Kota Semarang in 2014 and knowing the influence factors of this implementation. New Entrepreneur Program has been part of Gerdu Kempling starting in 2011. There are three locations in this research: Village of Bulusan, Ngadirgo and Padangsari. This research using qualitative descriptive research methods. The subject in this study consisted of eight (8) informants. The results showed that the implementation of New Entrepreneur Program are still less effective that is seen from the precision implementation aspects. The factors that influence the implementation such as the goals and basic of policy, resource policy, communication and implementation activities, the implementing agency characteristics, external conditions as well as the disposition of the implementor are still less optimal too. Based on these conclusions, the researcher recommend to the implementation agency and target of this program need high commitment and take maximal advantages for sustainable in order to achieve the purpose of this program.